Intern Nursing Students' Death-Related Anxiety, Compassion Levels, and Views on End-of-Life Care. - Yilmaz, Beyza; Adadioglu, Oznur (International Journal of Caring Sciences)
Background: Assessing the death anxiety and compassion levels of nursing interns, who will play a crucial role in providing healthcare services, is essential for raising their awareness about these issues, fostering positive attitudes toward death, and enhancing the quality of care for dying patients. Purpose: The purpose of this study is to determine nursing students' death anxiety, compassion levels and attitudes toward giving care to the dying. Methodology: The sample of this descriptive correlational study comprised of 148 intern nursing students receiving education during the spring term of the 2023-2024 academic year. The data were collected via "The Participant Information Form", "The Compassion Scale", "The Frommelt Attitude toward Care of the Dying Scale (FATCOD)" and "The Death Anxiety Scale". Results: The female students had a higher level of death anxiety (p<0.05). The nursing students who had faced death in their clinic and desired to take care of the dying had higher mean FATCOD scale scores. A correlation was found between the participants' Compassion Scale scores and FATCOD scale scores in a positive way (p<0.01). A correlation was found between the participants' Death Anxiety Scale scores and FATCOD scale scores in a negative direction (p<0.05) Conclusion: As the students' compassion levels increased and death anxiety decreased, their positive attitudes toward giving care to the dying increased. It is possible to update course contents and arrange trainings to increase the compassion levels and decrease the death anxiety of students. By this way, future nurses who are aware of their own feelings about death and can manage death anxiety may become more compassionate and professional in care of the dying and contribute to the increase of care quality.